Sensory Quality Analysis and Physical Quality of Pasta Butterflies Arrowroot Starch Substitution - Riya Anna Nathashia Tanamal (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to examine and analyze the effect of arrowroot starchsubstitution on the sensory and physical quality of farfalle pasta. Theresearch was conducted at the Pastry and Bakery Laboratory,Culinary Arts Education Study Program, Universitas Negeri Jakarta,from July 2024 to June 2025. A quantitative approach was usedthrough an experimental method, followed by an organoleptic testinvolving 45 semi-trained panelists, who were Culinary ArtsEducation students, Universitas Negeri Jakarta that had completedthe organoleptic evaluation course. The arrowroot starchsubstitution levels used were 30%, 40%, and 50%. Descriptiveanalysis results showed the highest scores in the following aspects:dry farfalle pasta color at 30% substitution with a score of 4.5categorized as golden yellow category and rated as first-best; drypasta aroma at 30% substitution with a score of 4.3 categorized asfree from arrowroot odor and rated as second-best; dry pasta textureat 30% substitution with a score of 4.5 categorized as firm and ratedas first-best; cooked farfalle pasta color at 30% substitution with ascore of 4.0 categorized as pale yellow and rated as second-best;cooked pasta aroma at 30% substitution with a score of 4.3categorized as strongly free from arrowroot odor and rated assecond-best; cooked pasta texture at 40% substitution with a score of4.4 categorized as chewy and rated as second-best; and cooked pastataste at 30% substitution with a score of 4.0 categorized as slightlytasting of arrowroot and rated as second-best. Physical quality testsshowed no significant effect on water absorption capacity andmoisture reduction. In conclusion, the best product was farfalle pastawith a 30% arrowroot starch substitution